Assessing bare-soil evaporation from different water-table depths using lysimeters and a numerical model in the Ordos Basin, China - Ma, Zhitong; Wang, Wenke; Zhang, Zaiyong; Brunner, Philip; Wang, Zhoufeng; Chen, Li; Zhao, Ming; Gong, Chengcheng (My University, 2019)
In semiarid and arid regions, the evaporation from bare soil is highly sensitive to changes in the depth to the water table. This study quantifies the relation between water-table depth and the groundwater contribution to evaporation in the Ordos Basin in China. In-situ field experiments were combined with numerical simulations of heat, vapor and liquid water flow. Based on lysimeter experiments and a calibrated numerical model, a relation between depth to groundwater and evaporation rate was established for the lysimeter site. In addition, a sensitivity analysis considering the hydraulic conductivity and the inverse of the air-entry pressure (vanGenuchten α) was established. For the field site, the results showed that for the water-table depths less than 52 cm below the ground, evaporation is independent of the water-table depth. For water-table depths exceeding 52 cm, an exponential relation between depth to groundwater and evaporation is observed. No phreatic evaporation occurs for water tables deeper than 105 cm, which is nearly two times the capillary fringe height. The sensitivity analysis showed that the extinction depth decreased with decreasing hydraulic conductivity and increased with α. The field-specific results and the sensitivity analysis provide valuable information to understand the dynamic processes of soil evaporation in the Ordos Basin. From a methodological point of view, the proposed modelling approach and the integration of lysimeter data proved to be a highly efficient combination to study evaporation dynamics in semi-arid and arid environments.
Keywords: Soil evaporation; Extinction depth; Numerical modeling; Lysimeter; Arid-region